The effectiveness of post-discharge navigation added to an inpatient addiction consultation for patients with substance use disorder; a randomized controlled trial. Issue 4 (October 2021) - Wakeman, Sarah E.; Rigotti, Nancy A.; Herman, Grace E.; Regan, Susan; Chang, Yuchiao; Snow, Rachel; Isenberg, Benjamin; Metlay, Joshua P.
Background: It is unknown whether post-discharge navigation enhances the impact of hospital-initiated addiction care. This study tested the incremental benefit of telephonic linkage to a post-discharge navigator for patients who received an addiction consultation during hospitalization. Methods: A two-arm, randomized controlled trial of 395 hospitalized adults with substance use disorder who received an addiction consultation. The intervention group received post-discharge phone calls from a navigator to review the recommended treatment plan and address barriers to engagement on days 3, 7, 14, and 21. The primary outcome was days of alcohol or drug use in the past 30 assessed by Timeline Follow-back at 1 month. Results: Follow-up assessment completion rates were 46% at 1 month, and 41%, at 2 months. At baseline, intervention and control groups did not differ in substance use patterns; 45% reported primary alcohol use, 43% drugs, and 12% both. Heroin was the most common drug. At baseline, mean days of past 30-day alcohol or drug use were 13.6 in the intervention and 14.9 in the control group. The median number of navigation calls completed was 3 out of 4. At 1 month, both groups reported less use (decrease of 4.8 in intervention vs. 4.2 days in control group, p = 0.49). There were no differences between groups at 2 months. Compared to controls, participants who received all four calls had a greater decrease in use with a mean 8.6 days decrease from baseline (difference of 4.4 days, p = 0.0009). Conclusion: Post-discharge telephonic patient navigation did not further improve substance use outcomes following addiction consultation.